Powers of Private Security Officers in Serbia and Human Rights and Freedoms: Some Dilemmas and Possible Solutions - Leštanin, Branko; Nikač, Željko (NBP. Nauka, bezbednosti, policija, 2025)
In modern society and the state, the delegation of the levers of power is noticeable, especially the possibility of applying coercion, which is also observed in the field of private security. As it is a new approach in practice, it causes certain dilemmas. In order for the level of respect for human rights and freedoms to be at a reasonable level during the exercise of powers by private security officers, certain principles that the authors arrive at by abstracting legal norms must be respected. In order to better understand the relationship between the powers of public authorities and private security, the authors tried to reach certain conclusions using the comparative law method. Most controversies are caused by powers that are enforced in practice but are not regulated by law (protection of crime scene, regulating traffic and identifying the presence of alcohol and other psychoactive substances in the body), so the authors tried to find the best possible solutions through observation with participation. It is concluded that the best solution is to regulate the enforcement of these powers through amendments to the law.